Beneficial Effects of Kiatsu™ with Ki Training on Episodic Migraine: An Exploratory Study - Calvin Y. Tabata (Hindawi Limited, 2021)
Objective. To conduct an exploratory study of KiatsuTM with Ki training as a potential therapy for treating episodic migraine in women. Background. Current therapies for migraine have proven partially effective, highlighting the need for alternative treatment options. In preparation for development of a randomized controlled study, the authors conducted a single arm pilot exploratory study to evaluate the effect of Kiatsu with Ki training in adult females with episodic migraine. Methods. Study subjects established a baseline migraine frequency over 4 weeks. During the following 4 weeks, each subject received instruction in Ki training (to improve concentration, balance, and relaxation), accompanied by Kiatsu (a focused touch method that reduces tension, swelling, and pain). Subjects then participated in one session a month for additional 6 months. The initial session was 1 hour; subsequent sessions averaged 30 minutes. Subjects documented migraine frequency, migraine-specific quality of life scores, and medication use. Result. Sixty-nine subjects met the study inclusion criteria, and 21 completed the study. Subjects reported a significant reduction in migraine frequency after 1 month (from 7.2 to 3.8 migraines/month; p<0.05), with an overall 53% reduction at 6 months (p<0.001). Significant improvements in quality of life (QoL) were reported after 1 month, with continued improvements until study completion (p<0.0001). A moderate reduction in medication use was also documented (p<0.03), corresponding to improved QoL scores. Conclusion. Kiatsu with Ki training may be an effective treatment option for females with migraines, either in combination with medications or as a potential alternative to medications for patients who do not benefit from conventional therapies. The results of this pilot study justify the development of a randomized controlled study designed to investigate the potential benefits of this novel therapeutic method for treating migraine.